2020
DOI: 10.1002/prot.26032
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and crystal structure of YhdA‐type azoreductase from Bacillus velezensis

Abstract: Azoreductases are being extensively investigated for their ability to initiate degradation of recalcitrant azo dyes through reduction of azo bonds. There is great interest in studying their diversity, structure, and function to facilitate better understanding and effective application. Current study reports azoreductase enzyme from Bacillus velezensis, which showed 69.5% identity to the Bacillus subtilis azoreductase YhdA. The enzyme was homotetrameric and molecular weight of each subunit was 20 kDa. It decolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…In contrast to heat-inactivated intracellular extracts, the activity of the enzyme was enhanced in the range of 2−4-fold in the presence of methyl red (MR) dyes, which was in accordance with documentary views that azoreductase largely exists in various quaternary forms, from dimers of Enterococcus faecalis and E. coli to tetramers of Bacillus subtilis and S. aureus. 33 The above results validate the drug release characteristic of Ag-TA-CON@EBS@PEG in response to bacteria. To our hypothesis, this characteristic of bacteria could be employed to develop bacteria-induced antimicrobial treatments.…”
Section: Enzyme-responsive Drug Release Studysupporting
confidence: 75%
“…In contrast to heat-inactivated intracellular extracts, the activity of the enzyme was enhanced in the range of 2−4-fold in the presence of methyl red (MR) dyes, which was in accordance with documentary views that azoreductase largely exists in various quaternary forms, from dimers of Enterococcus faecalis and E. coli to tetramers of Bacillus subtilis and S. aureus. 33 The above results validate the drug release characteristic of Ag-TA-CON@EBS@PEG in response to bacteria. To our hypothesis, this characteristic of bacteria could be employed to develop bacteria-induced antimicrobial treatments.…”
Section: Enzyme-responsive Drug Release Studysupporting
confidence: 75%
“…In Bacillus sp. AzoR in monomeric form, FMN has been found to be bound in the loop pocket [15,59]. These insights also lead to the idea that AzoR in Serratia sp.…”
Section: 5impact Of Reducing Factors On Degradationmentioning
confidence: 83%
“…Lys85, Val130, Thr131, and Arg33 form hydrophobic interaction with oxygen atoms of FMN while Ser86 formed a hydrophobic interaction with the carbon atom of FMN. The pattern of FMN binding was compared to Bacillus valezensis [59], and common interacting residues were Arg and Thr (although hydrophobic interactions instead of hydrogen bonding were observed). Hydrogen bond interactions of the Chromobacterium violaceum [61],…”
Section: 7hydrogen and Hydrophobic Interactions In Dye Degradationmentioning
confidence: 99%
“…Bacillus velezensis is known for its possession of azoreductases which are used to decolourise azo dyes of different molecular structures through enzymatic action 26,27 . It was also reported that B. velezensis contains a biopolymer that was isolated and used to decolourise azo dyes by bio-flocculation, with 91% efficiency 28 .…”
Section: Resultsmentioning
confidence: 99%